Avaliação de implantes tipo grampo para reinserção do manguito rotador - Carmo, Thiago Corrêa do (2017)
Aim: To assess the mechanic behavior of a new type of implant for the fixation of the rotator cuff without using sutures, regarding its insertional resistance and pullout strength. Materials and methods: The new implant’s geometry is clamp-type, although with ridges for locking. We assess three different configurations of clamp implants, varying a number of rods, the number of ridges and the base shape. We assessed the mechanical resistance of the implants considering the maximum load levels during insertion in a block with mechanic properties similar to bone. For this analysis, we developed an experimental apparatus in order to simulate impacts on the superior base of the implants. The pullout strength was assessed through a universal testing machine (MTS) using an experimental apparatus to simulate the traction on the tendons fixed to the block. We used controlled resistance bands to simulate the tendons. Results: A total of 21 implants were inserted in the block. Four implants failed during insertion. During insertion, the round head, three rods implant (type 3) needed a force of 149.0 N against 108.3 N for the two rods implant (type 1) and 119.2 N for the round head, 2 rods implant (type 2). The pull-out resistance to the round head, 2 rods implant (type 2) was higher than the other types of implants with an average value of 292.9 N, while the type 1 implant resisted with an average force of 165.2 N and type 3 with an average force of 135.2 N. Conclusion: Through testing, we can conclude that the type 2 implant has better mechanical features than the other two types of implants we tested, and its levels of force were consistent with its use in clinical practice. Clinical Relevance: An implant that eliminates the tendon-suture contact, transferring it to the implant may lead to a decrease in suture failures when repairing the rotator cuff and consequently reduce surgery time and cost, since the surgery would be simpler and can be performed in less time, due to not using sutures. These new implants can also be used as supports in traditional surgery aiming to increase the tendon’s fixation resistance. For final validation, there is still a need for clinical testing for the verification of the results.